Tinjauan Yuridis Mekanisme Pengawasan Dan Penanganan Sengketa Pelanggaran Merek Di Marketplace Digital di Indonesia - I Gusti Agung Ngurah Gede Wisnu Wardhana; I Gede Agus Kurniawan (Bacarita Law Journal, 2025)
The rapid development of digital commerce in Indonesia through online marketplaces has posed significant challenges to the protection of intellectual property rights, particularly trademarks. Trademark infringements in the form of counterfeit product sales and unauthorized use of marks are increasingly prevalent, while the mechanisms for supervision and dispute resolution remain less than effective. This situation is further complicated by the ambiguity regarding the legal liability of electronic system providers (marketplaces) as stipulated under the Electronic Information and Transactions Law (UU ITE), creating a legal grey area when juxtaposed with the Trademark and Geographical Indications Law. This study aims to examine the juridical mechanisms of supervision and the forms of dispute resolution for trademark infringements in digital marketplaces, as well as to analyze the implications of unclear marketplace liability under the UU ITE. The research employs a normative legal method with a statute-based approach, focusing on the review of relevant legislation, scholarly literature, and judicial decisions. The findings reveal that although the Trademark Law provides a legal basis for protection and dispute settlement through both litigation and non-litigation mechanisms, its implementation within digital marketplaces remains weak due to the absence of explicit provisions concerning marketplace liability. This lack of clarity generates a legal vacuum that potentially undermines certainty for trademark holders, consumers, and the marketplaces themselves. The originality of this research lies in its critical analysis of the grey area between the UU ITE and the Trademark Law, a subject rarely explored in prior studies, and in highlighting the urgency of regulatory harmonization to strengthen trademark protection within Indonesia’s digital trade ecosystem.